Analysis of Transmitted and Received ECG Signal Based on Internet of Thing Using Web Browser and Server-Client HTML Protocol - Dewi Rushalina; I Dewa Gede Hari Wisana; Priyambada Cahya Nugraha; Nazila Ragimova (Jurnal Teknokes, 2022)
Cardiovascular disease is one of the leading causes of death worldwide. One of the reasons for the large number of deaths from heart disease is the lack of regular cardiac monitoring. Electrocardiograph (ECG) is a method of monitoring heart conditions. There are still many ECG examinations in hospitals that are carried out directly in certain places and the results can only be seen at that time. Meanwhile, when negligence or carelessness occurs, it can endanger the patient due to delays in handling. One of the efforts that can be made to improve service to heart patients is by having ECG monitoring based on IoT (Internet of things). The purpose of this study is to analyze the ECG signals sent and received by IoT media so that they are useful for the diagnostic process. The contribution of this research is to know the shape of the ECG signal that is sent and received through IoT media. The procedure to achieve this goal is with the AD8232 sensor whose output will be processed through the microcontroller and displayed on computer and smartphones via IoT. From this research, the results obtained that the average value of lost data at BPM 60 and BPM 120 is quite good, namely 21.26% and 24.44%.hile the average time delay value at BPM 60 and BPM 120 is also quite good, namely 0.023 s and 0.03 s. So, it can be concluded that the sending of IoT-based ECG signals affects the form of signals sent and received. The results of this study are expected to be developed in further research with development in the form of adding leads or adding BPM parameters.